Ethnomedicine in Sabah : past trends and future perspectives - David Matanjun; Mohammad Saffree Jeffree; Freddie Robinson; Falah Abbas Mohamed Salih; Md Shamsur Rahman; Naing Oo Tha (2019)
Introduction: The objective of this presentation is to carry out a review of the historical status and possible future outlook of the practice of ethnomedicine in the State of Sabah. As in many parts of the world, there are many types of traditional medicines that have been used for hundreds of years among the various native cultural groups in Sabah. Methods: A literature survey was conducted with the aid of online database, and text books using keywords such as the current as well as previous names of Sabah and various related terminology such as ethnomedicine, CAM, complementary and alternative medicine, TCM, traditional and complementary medicine, herbalism, reflexology, spiritualism, ethnobiology ethnology, ethnoanthropology, biological activities, ethnobotanical uses, medicinal prop-erties, toxicity studies, etc. The status of ethnomedicine in Sabah is largely unknown. Results: Based on a review of previous literature, the study discovered that there is limited empirical documentation on the use of ethnomedicine in Sabah. In this preliminary review, a total number of 25 publications were recorded in the databases for the period up to 2019. There is still a need to realise the full potential of the biocultural diversity of Sabah, and that there is a strong need to focus more on socially relevant research. Ethnomedicine in Sabah consists mainly of herbalism, ma-nipulative practices and spiritualism. Plants can be said to be the central player in race-based traditional medicine. While data on ethnomedicine may be based on original field research, several are primarily derivative, drawing as they do from earlier published accounts and, importantly, anecdotes. Traditional massage and other manipula-tive-practices, based on manipulation and movement of body parts, are also popular because of their simplicity and apparent immediate relief that can be experienced by the patient or client. Spiritualism, which may be considered as a peculiar dimension of the mind-body medicine subset of traditional medicine, continues to have its adherents among the natives of Sabah. Conclusion: List and catalogs and sociological and ethnohistorical data were the fa-voured perspective of research in the past; but future evolution of ethnomedical studies need to address some of the debates related to biological, medical and social sciences . Future research should include systematic inves-tigation into efficacy and risk besides the possible incorporation of some parts of ethnomedicine into the existing healthcare services. Ethnomedicine occupies a distinct place in healthcare in the world in general, and Sabah in particular.